Exploring the Impact of Artificial Proprioception on Postural Stability in Individuals with Transtibial Prosthesis - Diaz-Hernandez, Octavio (Revista Mexicana de Ingenieria Biomedica, 2025)
This study investigates the effects of Artificial Proprioception (AP) on postural stability in transtibial amputees using a non-invasive mechatronic system. Eight participants with unilateral lower-limb amputation underwent stabilometric evaluations under four visual and sensory conditions (with/without AP, eyes open/closed) using a baropodometric platform. The AP system translated plantar pressure from instrumented insoles into vibrotactile feedback via actuators positioned on dermatome-mapped regions of the thigh. Time-series analyses, pressure maps, and center of pressure (COP) dynamics were assessed through metrics such as displacement, velocity, sway area, and Romberg indices. While statistical significance was not achieved, descriptive trends revealed a reduction in COP variability, particularly in eyes-closed conditions, suggesting enhanced postural control. The system’s proportional feedback and anatomical mapping may facilitate improved somatosensory integration and compensatory motor strategies. These findings support AP as a promising tool for balance rehabilitation in lower-limb amputees, warranting further study with larger cohorts and dynamic tasks.